Pendidikan Islam dan Tantangan Multikulturalisme: Penelitian - Eka Lindayati; Hasan Asy’ari; Yulita; Hilmin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic education plays a strategic role in shaping the character and morals of students based on Islamic values. Amid the dynamics of increasingly pluralistic and multicultural societies, Islamic education faces the challenge of adapting without losing the essence of its teachings. Multiculturalism demands that Islamic education be more inclusive, tolerant, and open to diversity. This study employs a qualitative descriptive approach to examine how Islamic education responds to the challenges of multiculturalism and the strategies that can be implemented in the learning process. The findings indicate that strengthening universal Islamic values such as tolerance, justice, and compassion is essential to building social harmony. Furthermore, curriculum development sensitive to multicultural contexts and teacher training with a pluralistic perspective are strategic steps to deliver relevant Islamic education in the era of globalization. Thus, Islamic education functions not only as a medium for transmitting knowledge and religious values but also as an agent of peace and social integration in pluralistic societies.